2013
DOI: 10.1099/vir.0.052555-0
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics and in vitro antibody pressure of porcine parvovirus indicate a decrease in variability

Abstract: To estimate the impact of porcine parvovirus (PPV) vaccines on the emergence of new phenotypes, the population dynamic history of the virus was calculated using the Bayesian Markov chain Monte Carlo method with a Bayesian skyline coalescent model. Additionally, an in vitro model was performed with consecutive passages of the 'Challenge' strain (a virulent field strain) and NADL2 strain (a vaccine strain) in a PK-15 cell line supplemented with polyclonal antibodies raised against the vaccine strain. A decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Furthermore, the occurrence and distribution of new antigenic types have to be watched very closely. It was observed that new mutations in the capsid protein can modify antigenic properties, and may reduce the cross neutralization ability of sera raised against strains commonly used in commercial vaccines (Zeeuw et al, 2007;Streck et al, 2013Streck et al, , 2015a. New vaccines that induce a long-lasting immunity and cover all the dominant virus strains circulating in pig populations are needed to overcome currently observed putative vaccination failures.…”
Section: Control Of the Virus (Including Vaccine And Antiviral Research)mentioning
confidence: 99%
“…Furthermore, the occurrence and distribution of new antigenic types have to be watched very closely. It was observed that new mutations in the capsid protein can modify antigenic properties, and may reduce the cross neutralization ability of sera raised against strains commonly used in commercial vaccines (Zeeuw et al, 2007;Streck et al, 2013Streck et al, , 2015a. New vaccines that induce a long-lasting immunity and cover all the dominant virus strains circulating in pig populations are needed to overcome currently observed putative vaccination failures.…”
Section: Control Of the Virus (Including Vaccine And Antiviral Research)mentioning
confidence: 99%
“…Mutations found on immune selected capsids (NADL-2 I320S, H383Q; Str. Challenge S45T, P436S) were not present on novel variants either [ 45 ]. The authors concluded that vaccine failures and non-vaccinated animals (e.g., wild boars) may have a more important impact on the emergence of new phenotypes than vaccinated populations.…”
Section: Genetic Variation and Evolutionmentioning
confidence: 99%
“…Recently, a population dynamic analysis showed that, despite the high evolutionary rate, only a few PPV strains (similar to strain 27a) have been predominant in Europe in recent years (Streck et al, 2013b). For this reason, it is hypothesized that new PPV strains may interfere with the efficacy of the currently used vaccines (Truyen & Streck, 2012).…”
mentioning
confidence: 99%